Will the Euro Eventually Surpass the Dollar as Leading International Reserve Currency? - Chinn, Menzie D.; Frankel, Jeffrey A. (My University, 2006)
The euro is a plausible competitor to replace the dollar as the leading currency central banks hold, just as the dollar replaced the pound. Factors affecting the dollar's status include size of the home country, inflation, exchange rate variability and size of the relevant home financial center as measured by the turnover in its foreign exchange market. The euro's success will depend on whether the United Kingdom and enough other European Union members join euroland so it becomes larger than the U.S. economy and whether U.S. macroeconomic policy undermines confidence in the value of the dollar, in the form of inflation and depreciation. This paper is a substantial revision of an earlier work presented at a National Bureau of Economic Research conference on current account sustainability.